(untitled) (Global Journal of Science Frontier Research, 2023)
Shea butter is a significant source of fat in the diet of many rural dwellers in Nigeria It is produced from the seeds of Vitellaria paradoxa L tree Its suitability as dietary fat or use in cosmetic industry is greatly influenced by its physicochemical properties and fatty acid composition This study aimed at determining the physicochemical properties and fatty acid profile of shea butter found in Nigeria as a possible source of industrial raw material for the production of stearic acid The physicochemical analyses results showed that the saponification value of the shea butter samples ranged from 174 55 mg KOH g - 200 97 mg KOH while iodine value is from 42 22 g 100g - 98 46 g 100g the unsaponifiable matter ranged from 2 32 - 10 55 and peroxide value ranged from 8 14 meq kg - 19 66 meq kg From the result of the GC-MS analysis the dominant unsaturated fatty acids observed are oleic linoleic vaccenic and gamma linolenic gondoic and palmitoleic acids While the saturated fatty acids found are stearic palmitic arachidic behenic and lignoceric acids The data indicate that the Shea butter obtained from the Federal Capital Territory FCT Abuja and Niger state may be good sources of raw material for the production of stearic acid